Smart Armband for Early Detection of Hypothermia and Hypoxia with the Location Tracing System during Emergencies Based LoRa on Hikers - Raihan Zhifhanur Muhammad; Monika Ayu Puji Anggraini; Andi Nurul Isri Indriany Idhil; Muhammad Yogi Nurrohman; Rafa Raihan Fadilla; Zainul Abidin (International Journal of Science, Technology & Management, 2021)
Hiking has a dangerous risk of accidents and deaths of hikers. It is caused by health problems, lost, and other accidents. A LoRa-based smart armband was designed to detect hypothermia, hypoxia, and emergencies in hikers based on the above explanation. Furthermore, all activities can be monitored using a web accessed through smartphones or computers. If hypothermia and hypoxia are detected, the smart armband will remind the hiker. The IMU sensor will detect movement orientation and acceleration of the hiker during emergencies to be sent to the hiking post for evacuation. All activity data are stored in a micro-SD for evaluation. From the test results, the armband functioned at temperatures ?35ºC, air pressure ? 560,2 mmHg, and acceleration ?200 cm/s2. The test results also proved that the armband lasted up to 35 hours